Deciphering proteins and their functions in the regenerating retina. (October 2010) - Prokosch, Verena; Chiwitt, Carolin; Rose, Karin; Thanos, Solon
Neurons of the mammalian CNS, including retinal ganglion cells, lack, in contrast to the PNS, the ability to regenerate axons spontaneously after injury. Regeneration of the CNS is extremely complex and involves various molecular factors and cells. Therewith the regenerative process remains an enormous scientific and clinical challenge. This article provides an overview of proteins that play a crucial role in axon regeneration of retinal ganglion cells and their underlying signaling pathways. In this context, we elucidate the role of 2D gel electrophoresis and highlight some additional proteins, altered upon regeneration by using this highly sensitive method.